Pengurangan Isolasi Sosial pada Klien “DI” Pengidap Penyakit Skizofrenia Paranoid melalui Intervensi Social Skill Training - Ananda Lufi Nabila; Mari Esterilita (Politeknik Piksi Ganesha Indonesia, 2025)
Abstract: The prevalence of schizophrenia sufferers in Indonesia is in the range of 0.3% to 1% of the population, one of which is paranoid schizophrenia, which is the most common type with the main symptoms of delusions and hallucinations. Social isolation is one of the most common behaviors, covering around 72% of people with schizophrenia. This study aims to reduce the level of social isolation in clients